Immune Microenvironment on the Molecular Mechanisms and Therapeutic Targets of MAFLD - Jiang Z; Qian B; Xu T; Bai J; Fu W (ImmunoTargets and Therapy, 2025)
Zhonghao Jiang,1,* Baolin Qian,1,* Tongjie Xu,1,2 Junjie Bai,1 Wenguang Fu1,3 1Department of Biliary-Pancreatic Center, The Affiliated Hospital of Southwest Medical University, Luzhou, People’s Republic of China; 2Department of Vascular Surgery, The Affiliated Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China; 3Metabolic Hepatobiliary and Pancreatic Diseases Key Laboratory of Luzhou City, The Affiliated Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenguang Fu, Department of General Surgery (Hepatopancreatobiliary Surgery), The Affiliated Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China, Email fuwg@swmu.edu.cnAbstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) is one of the most prevalent chronic liver diseases worldwide. It is characterized by hepatic steatosis in the absence of significant alcohol consumption, and can progress to liver fibrosis, cirrhosis, and even hepatocellular carcinoma (HCC). Despite its widespread impact, treatment options remain limited, and effective therapies targeting the underlying disease mechanisms are lacking. Recent studies have highlighted the critical role of the liver’s immune microenvironment in the onset and progression of MAFLD. However, research into immune-based therapies remains in its early stages. Most existing studies have focused on understanding the immune mechanisms involved, but specific immune targets and therapeutic strategies have yet to be fully explored. This gap has hindered the development of targeted immunotherapies for MAFLD. This review aims to examine the molecular mechanisms of the immune microenvironment in MAFLD and identify potential therapeutic targets, offering insights for future clinical and scientific advancements.Keywords: MAFLD, immune microenvironment, pathway, therapeutic targets